2017
DOI: 10.1016/j.cell.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding Transcription Instructs Chromatin Folding and Compartmentalization to Dictate Enhancer-Promoter Communication and T Cell Fate

Abstract: SUMMARY It is now established that Bcl11b specifies T cell fate. Here we show that in developing T-cells the Bcl11b enhancer repositioned from the lamina to the nuclear interior. Our search for factors that relocalized the Bcl11b enhancer identified a non-coding RNA named ThymoD (Thymocyte Differentiation Factor). ThymoD-deficient mice displayed a block at the onset of T cell development and developed lymphoid malignancies. We found that ThymoD transcription promoted demethylation at CTCF bound sites and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
222
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(247 citation statements)
references
References 52 publications
23
222
1
1
Order By: Relevance
“…A role for elongation is also strongly supported by premature termination of the active Cobl gene by insertion of a PAS, which primarily caused an increase of NL interactions downstream but not upstream of the new termination site. These results are consistent with a study of the ThymoD non‐coding RNA gene in mouse T‐cell progenitors, where insertion of a PAS prevented detachment from the NL as observed by FISH (Isoda et al , ). Conversely, read‐through transcription into heterochromatin, elicited by influenza virus NS1 protein, was found to cause relocation from the heterochromatic compartment “B” to the euchromatic compartment “A” (Heinz et al , ), which largely correspond to LADs and iLADs, respectively (van Steensel & Belmont, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A role for elongation is also strongly supported by premature termination of the active Cobl gene by insertion of a PAS, which primarily caused an increase of NL interactions downstream but not upstream of the new termination site. These results are consistent with a study of the ThymoD non‐coding RNA gene in mouse T‐cell progenitors, where insertion of a PAS prevented detachment from the NL as observed by FISH (Isoda et al , ). Conversely, read‐through transcription into heterochromatin, elicited by influenza virus NS1 protein, was found to cause relocation from the heterochromatic compartment “B” to the euchromatic compartment “A” (Heinz et al , ), which largely correspond to LADs and iLADs, respectively (van Steensel & Belmont, ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations were made when VP64 (a tetramer of VP16) was tethered to promoters of three distinct genes in LADs in mouse embryonic stem (mES) cells (Therizols et al , ). Another study found that activation of the long non‐coding RNA gene ThymoD in mouse T‐cell progenitors contributed to the detachment of the neighboring gene Bcl11b from the NL (Isoda et al , ). The molecular signals that cause detachment of a locus from the NL are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There may also be a role for noncoding RNA in enhancer-promoter interactions 25,26,[78][79][80] . Notably, whilst mRNA has been shown to direct the formation of phase condensate compartments in the cytoplasm 81 and eRNAs have been proposed to play a similar role in the formation of enhancer-promoter complexes 25,26 our results following dissolution of phase condensates with hexanediol treatment argue that these interactions are not sufficient for maintaining contact at many genes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described how non-coding RNA (ncRNA) transcription at the Bcl11b enhancer caused Bcl11b gene activation along with release of the surrounding 2 Mb of chromatin from the NL (Isoda et al, 2017). ncRNA transcription was shown to promote DNA demethylation, binding of CTCF and cohesin, and the formation of chromatin loops, which were hypothesized to sequester the Bcl11b locus in a transcriptionally active compartment away from the NL.…”
Section: Discussionmentioning
confidence: 99%